Dissimilarity Between Dust, Heat, and Momentum Turbulent Transports During Aeolian Soil Erosion. Issue 2 (25th January 2019) - Dupont, S.; Rajot, J.‐L.; Labiadh, M.; Bergametti, G.; Lamaud, E.; Irvine, M. R.; Alfaro, S. C.; Bouet, C.; Fernandes, R.; Khalfallah, B.; Marticorena, B.; Bonnefond, J. M.; et al.
Abstract: Measuring accurately size‐resolved dust flux near the surface is crucial for better quantifying dust losses by semiarid soils. Dust fluxes have been usually estimated from the flux‐gradient approach, assuming similarity between dust and momentum turbulent transport. This similarity has, however, never been verified. Here we investigate the similarity between dust (0.3 to 6.0 μm in diameter), momentum, and heat fluxes during aeolian erosion events. These three fluxes were measured by the Eddy Covariance technique during the WIND‐O‐V (WIND erOsion in presence of sparse Vegetation's) 2017 field experiment over an isolated erodible bare plot in South Tunisia. Our measurements confirm the prevalence of ejection and sweep motions in transporting dust as for heat and momentum. However, our measurements also reveal a different partition of the dust flux between ejection and sweep motions and between eddy time scales compared to that of momentum and heat fluxes. This dissimilarity results from the intermittency of the dust emission compared to the more continuous emission (absorption) of heat (momentum) at the surface. Unlike heat emission and momentum absorption, dust release is conditioned by the wind intensity to initiate sandblasting. Consequently, ejection motions do not carry dust as often as heat and low momentum from the surface. This dissimilarity diminishes with increasing wind intensity as saltation patterns, and thus dust emission through sandblasting, become spatially more frequent. Overall, these findings may have implications on the evaluation of dust flux from techniques based on similarity with momentum or heat turbulent transport. Key Points: The near‐surface size‐resolved dust flux is estimated using the eddy covariance technique Dissimilarity between dust, heat, and momentum turbulent transports is observed due to the large intermittency of the dust emission Our findings have implications on the evaluation of dust flux using techniques based on similarity with momentum‐heat turbulent transport